PENGARUH SUSTAINABILITY REPORTING DAN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DARI SISI MARKET VALUE RATIOS - Dian Avita Sari; Nur Azlina; Mudrika Alamsyah Hasan (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
This study aims to find out about (1) the influence of economic, environmental and social sustainability reporting on the company's financial performance in terms of market value ratios, (2) the influence of intellectual capital on the company's financial performance from the market value of ratios.The research method used is explanatory which aims to explain the relationship between variables through data analysis in order to test hypotheses. Sustainbility report independent variable in this study consists of 3 aspects, namely economic, environmental, and social, measured by using the SRDI index. While intellectual capital is measured by VAIC and the dependent variable financial performance is measured by market value ratios. The research sample was 15 LQ45 companies that published sustainability reports, had positive profits and published financial reports for 2014-2016. Hypothesis testing is carried out using the Structural Equation Model (SEM) approach. Statistical test tools used are Smart PLS programs ver.3 and microsoft Excel 2010. The results showed that the sustainability reporting variable from the economic aspect had no effect on the financial performance in terms of market value ratios, while the sustainability reporting variable from the environmental aspect and social aspects each had positive and negative effects and intellectual capital variable has a positive effect on the company's financial performance in terms of market value ratios